Four Innovative Teaching Methods. Is There a Place for Post-Pedagogy? - Chukurliev, Hristo (English Studies at NBU, 2024)
The article examines the need for a new pedagogical framework in the context of contemporary higher education, influenced by digital innovations and generational change. It introduces four innovative pedagogical approaches – Description of an Object, Humanities Laboratory, Venus of Slatina, and Time Machine – which serve as a basis for discussing ’post-pedagogy’. The approaches are united by the goal of achieving priorities such as interdisciplinary training, critical thinking, and the encouragement of curiosity. By proposing the integration of these methods, the article aims to draw attention to the changed landscape of the educational field.